The effect of labour hopscotch framework on maternal and neonatal outcomes in pregnant women: A randomized controlled trial - Saeedeh Askari; Mina Iravani; Parvin Abedi; Bahman Cheraghian; Eesa Mohammadi; Shayesteh Jahanfar (PLoS ONE, 2025)
The Labour Hopscotch Framework (LHF) is a practical tool designed for women to use with the support of their birthing partners throughout labor and birth. It was specifically developed to help midwives support women in achieving a physiological birth. We conducted a randomized controlled trial to evaluate the impact of the LHF on maternal and neonatal outcomes. The study took place from March 2023 to October 2023 in Ahvaz, Iran. A total of 124 primiparous women with full-term pregnancies were recruited and randomly allocated to either the intervention or control group. Eligible participants for the study included women who were 18 years of age or older, had cephalopelvic proportions within normal limits, were carrying low-risk singleton pregnancies, and had attended childbirth education classes. Women were excluded if they had contraindications for vaginal birth, were carrying a fetus with abnormalities, or had medical conditions that could complicate childbirth. Birth mode, average duration of the labor phases, maternal and neonatal outcomes, and overall childbirth satisfaction were assessed as outcomes. Women who used the LHF experienced shorter labor durations compared to the control group (d =  -1.3 min, 95% CI: -1.6 to -0.8). Women using the LHF were 10.3 times more likely to experience a vaginal birth (OR =  10.3, 95% CI: 1.3-88.5, p = 0.030). Women in the LHF group initiated breastfeeding earlier than those in the control group (OR = 20.4, 95% CI:7.7-53.3, p < 0.001), but no difference between the two groups for exclusive breastfeeding (p = 0.496). Two groups did not show any significant difference in neonatal outcomes. The mean satisfaction score was higher among women with LHF compared to women in the control group (d = 2.3, 95% CI: 1.8 to 2.8), p < 0.001). The LHF can increase the rate of physiological births and reduce the duration of the labor phases. Also, women were more satisfied with their birth experiences. Trial registration ClinicalTrials.gov IRCT20161106030750N2